2019
DOI: 10.1111/jcmm.14639
|View full text |Cite
|
Sign up to set email alerts
|

miR‐20a‐5p regulates pulmonary surfactant gene expression in alveolar type II cells

Abstract: MicroRNA (miRNA) critically controls gene expression in many biological processes, including lung growth and pulmonary surfactant biosynthesis. The present study was conducted to investigate whether miR‐20a‐5p had such regulatory functions on alveolar type II (AT‐II) cells. To accomplish this, miR‐20a‐5p–overexpressed and miR‐20a‐5p–inhibited adenoviral vectors were constructed and transfected into cultured AT‐II cells that were isolated from rat foetal lungs of 19 days' gestation. Transfection efficiency was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…In fact, our analysis of the AFSC-EV miRNA cargo and downregulated genes revealed 28 miRNAs that play a role in restored epithelial and mesenchymal cell differentiation, as well as branching morphogenesis. As an example, miR-20-5p, which belongs to the miR17~92 family, is of particular interest as it controls pulmonary surfactant gene expression in AT2 cells [55]. In addition to this cluster, miR-28-5p was also found in our network to regulate Robo1 and Pdgfra , and has been reported to be decreased in the nitrofen model of CDH [7,56].…”
Section: Discussionmentioning
confidence: 97%
“…In fact, our analysis of the AFSC-EV miRNA cargo and downregulated genes revealed 28 miRNAs that play a role in restored epithelial and mesenchymal cell differentiation, as well as branching morphogenesis. As an example, miR-20-5p, which belongs to the miR17~92 family, is of particular interest as it controls pulmonary surfactant gene expression in AT2 cells [55]. In addition to this cluster, miR-28-5p was also found in our network to regulate Robo1 and Pdgfra , and has been reported to be decreased in the nitrofen model of CDH [7,56].…”
Section: Discussionmentioning
confidence: 97%
“…As an example, miR-20-5p, which belongs to the miR17~92 family, is of particular interest as it controls pulmonary surfactant gene expression in AT2 cells. 57 Through antagomir studies, we demonstrated that miR-20-5p is responsible for AFSC-EV rescue effect of impaired autophagy, a key cellular mechanism that is dysregulated in CDH lungs. 58 In addition to this cluster, miR-28-5p was also found in our network to regulate Robo1 and Pdgfra , and has been reported to be decreased in the nitrofen model of CDH.…”
Section: Discussionmentioning
confidence: 91%
“…For example, decreased miRNA biogenesis by silencing Drosha enhanced the potential of human alveolar type II cells to secrete SP-A protein [30]. Furthermore, several in vitro or in vivo studies revealed that miRNAs such as miR-200 family [31], miR-29 [32], miR-20a-5p [33], and miR-16 [34] positively regulate pulmonary surfactant proteins synthesis whereas miR-431-5p [30], miR-199a/214 cluster [36], miR-26a [37][38][39], miR-206 [40] were found to exert an inhibitory role in AECII differentiation and synthesis of surfactant proteins (Table 3). Interestingly, it has been also reported that SP-A2 (SP-A has two variants: SP-A1 and SP-A2) regulates miRNome of alveolar macrophages (AM) in a sex-specific manner.…”
Section: Mirna-clr Axes In Developmental and Physiological Homeostasismentioning
confidence: 99%